2010
DOI: 10.1002/acr.20034
|View full text |Cite
|
Sign up to set email alerts
|

What outcomes from pharmacologic treatments are important to people with rheumatoid arthritis? Creating the basis of a patient core set

Abstract: Objective. Function, patient global assessment, and pain are routinely measured in rheumatoid arthritis (RA) clinical trials. However, other patient-reported outcomes identified as important to patients in qualitative studies, such as fatigue and quality of life, are commonly not included, and modern treatment regimens may have changed patients' expectations of treatment outcomes. Our objective was to elicit patient priority treatment outcomes for pharmacologic interventions since the common use of anti-tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 20 publications
3
126
0
Order By: Relevance
“…For patients, more understandable treatment goals are relief of physical symptoms and achieving optimal physical and social functioning. 11,12 Our study shows that joint swelling without pain or progression of erosions sometimes is not linked to disease activity by patients. Particularly, older patients may not perceive abnormal joints or be unaware of the importance of the presence of swollen joints in the assessment of RA activity.…”
Section: Discussionmentioning
confidence: 73%
“…For patients, more understandable treatment goals are relief of physical symptoms and achieving optimal physical and social functioning. 11,12 Our study shows that joint swelling without pain or progression of erosions sometimes is not linked to disease activity by patients. Particularly, older patients may not perceive abnormal joints or be unaware of the importance of the presence of swollen joints in the assessment of RA activity.…”
Section: Discussionmentioning
confidence: 73%
“…The priority of Visible joint damage provided the greatest challenge because no existing instrument could be found that measured patients' selfreporting of joint damage. The three NRS were developed from previous interview data [17], and discussed during the consultation meetings and focus groups. A minority of Phase 1 participants were concerned about the effect of the term 'joint damage' on newly diagnosed patients, but the overall consensus was that RA patients should be realistic about the potential consequences of progression of their disease and the implications for measurement were more important.…”
Section: Discussionmentioning
confidence: 99%
“…A strength is that these new outcome measures are based on the development of a conceptual framework grounded in patient data from a previous study [17], in collaboration with patients as recommended by the FDA [10], and benefiting from a higher level of user involvement [47]. Further research aims to construct a final tool, which will assess priorities important to patients in one instrument, constructing an algorithm from observational data to produce a single score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations